Análise dos recursos financeiros destinados à assistência estudantil: estudo de caso do IFFar, no período de 2014 a 2019 - Weizenmann, Fabiane Barbosa de Almeida (2021)
Higher education enrollments in Brazil have shown a considerable increase, due to the various policies of the Federal Government and actions aimed at improving access to undergraduate courses. Among these actions, we highlight the implementation of REUNI and Federal Institutes, which expanded the number of vacancies, and also, the creation of PNAES, which provided more chances to students with socioeconomic difficulties to enter a higher education course. However, together with the initiatives to expand undergraduate courses, there was a concern about the resources needed to help students stay and complete their courses, notably from the year 2008, a period in which the country experienced a drop in tax revenues and continued growth in public spending, resulting in fewer resources available for investment in government policies. In this scenario, the policy of attending students, almost entirely conditioned to budgetary issues, started to have its goals contingent, and the federal educational institutions needed to review and redesign their strategies. In this way, this dissertation has as main objective to analyze if the financial resources influenced in the execution of the actions of AE. To this end, the methodology of this study consisted of bibliographic research, document analysis and case study, with the application of structured questionnaires, applied to the Student Assistance Coordinators (CAE) of all the institution's campuses. The conclusion of the research is that, at IFFar, all efforts were expended in preparing the planning of AE's actions, however, the constant cuts in transfers, carried out by the MEC, made it impossible to achieve some of the stipulated goals. There was a reduction in the budget allocated to IFES, in the areas of investments and costs, affecting the maintenance of routine activities and teaching, research and extension actions. The resources destined to AE showed positive growth, throughout the period, allowing an increase in the number of attendances, but being practically destined to meet the demands of food, aid, transportation and student housing. The funds from budget source 2994 (Assistance to IFE Students) were insufficient for all student demands, requiring complementation with other sources. Although IFFar operates in a context of budgetary constraints, with constant cuts in resources, needs for relocations and rescheduling, AE carried out important actions foreseen in the PNAES, and even working in a scenario of insecurities and uncertainties, there is a general mobilization in order to meet the demands of students in conditions of economic and social vulnerability.